FACILITY LAYOUT REDESIGN WITH SERVICE QUALITY AND 5S METHOD AT AHDA FARMA DRUG STORE IN ERA OF THE COVID-19 PANDEMIC - Umi Zulfa Nadia; Ida Betanursanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Ahda Farma Drug Store is a health service facility to meet the needs of the community regarding the importance of drugs and medical devices. To create an atmosphere and improve the quality of service, this research was carried out by redesigning the layout of drug store facilities. This study aims to identify the quality of service and redesign the layout of the facilities at the Ahda Farma Drug Store. The method used in this research is service quality and 5S (seiri, seiton, seiso, seiketsu and shitsuke). The results of the descriptive analysis identified problems in nine variables. Among other things tangible (physical evidence) pharmacies have enough seats, employees wear identification, a large parking area. Empathy (empathy) employees are attentive by asking customer needs, employees are polite and friendly. Reliability (reliability) of drug delivery services.Responsiveness (responsiveness) employees have good communication, pharmacies do not provide employees at certain times. Assurance (guarantee) pharmacies provide returns if the goods purchased are wrong. The results of the analysis using the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) are designed for prescription reception rooms, prescription and compounding service rooms, drug delivery rooms, counseling rooms, storage rooms for drug preparations, medical devices, and medical consumables,and archive space.